O direito a ter direitos efetivos : as dimensões normativas e eficácia do direito fundamental social à assistência jurídica integral e gratuita de titularidade dos indivíduos e grupos sociais necessitados (ou vulneráveis) à luz do atual regime jurídico constitucional e infraconstitucional da Defensoria Pública brasileira - Fensterseifer, Tiago (2016)
The aim of this thesis is to undertake study on the current constitutional and infra-constitutional legal regime of the Public Defender in Brazil, including through the prism of his new position in the Justice System. Under the new institutional legislative scenario opened by Constitutional Amendment 45/2004 (Reform of the Judiciary), and complemented, among other legal instruments, by the Federal Law 11.448/2007 (which established its legitimacy to the class action), by the reform of the National Law of Public Defense – Federal Law 80/94 (held by the Federal Law 132/2009), by the Constitutional Amendment 74/2013 (Constitutional Autonomy of Federal Public Defense), by the Constitutional Amendment 80/2014, and by the New Civil Procedure Code (Law 13.105/2015), sets to the Public Defense a new paradigm of assignments and role to play in the Justice System, breaking with its classic liberal individualistic design - focused almost exclusively on individual judicial action in criminal law - for the sake of legitimacy to act, both at the individual and collective procedure, in the protection and promotion of fundamental rights of all generations or dimensions (liberal, social and ecological) of ownership of those in need (both economic and organizational perspective). In light of this new regulatory framework, the thesis develops the consecration of the fundamental social right to full and free legal assistance ownership of individuals and needy social groups (or vulnerable) in the Federal Constitution of 1988 (art. 5, LXXIV), including it as content of the fundamental right-guarantee the existential minimum (minimum core obligation). Based on the public model for providing legal assistance to those in need through the Public Defender enshrined in our Constitution (art. 134), the State (State-Legislator and State-Administrator), both at the federal and state levels, the progressivity duty to ensure proper structuring the institution, under penalty of judicial intervention in the case of omission or insufficient performance (under the principle of proportionality).